2021
DOI: 10.1111/ctr.14393
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2014 kidney allocation system changes on trends in A2/A2B into B kidney transplantation and organ procurement organization reporting of donor subtyping

Abstract: The current kidney allocation system (KAS) preferentially allocates kidneys from blood type A2 or A2B (A/A2B) donors to blood type B candidates. We used national data to evaluate center-level performance of A2/A2B to B transplants, and organ procurement organization (OPO) reporting of type A or AB donor subtyping, in 5-year time periods prior to (2009)(2010)(2011)(2012)(2013)(2014) and following (2015-2019) KAS implementation. The number of centers performing A2/A2B to B transplants increased from 17 pre-KAS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…13 The KAS, implemented on December 4, 2014, was designed to decrease disparities in transplantation by implementing new changes to the allocation algorithm, including allocating blood subgroup A2/A2B deceaseddonor kidneys to candidates with blood type B. 14 This change was made on the basis of improved long-term survival outcomes when the OPTN implemented variance of practice policies in 2002 to allow DDKT with A2 donors to B recipients. This prospective variance study showed an increase in access to kidney transplantation for minority candidates by as much as 36%, depending on donor service area in the study.…”
Section: Implementation Of the Kas To Decrease Disparitymentioning
confidence: 99%
See 4 more Smart Citations
“…13 The KAS, implemented on December 4, 2014, was designed to decrease disparities in transplantation by implementing new changes to the allocation algorithm, including allocating blood subgroup A2/A2B deceaseddonor kidneys to candidates with blood type B. 14 This change was made on the basis of improved long-term survival outcomes when the OPTN implemented variance of practice policies in 2002 to allow DDKT with A2 donors to B recipients. This prospective variance study showed an increase in access to kidney transplantation for minority candidates by as much as 36%, depending on donor service area in the study.…”
Section: Implementation Of the Kas To Decrease Disparitymentioning
confidence: 99%
“…However, 157 transplant centers did not perform a single A2/A2B to B transplant at this time. 14 More importantly, they found that from 2015 to 2019, only 56.4% of A/AB donors were subtyped after implementation of the KAS. 14 The authors also found that 1161 A/AB donors went unrecognized as possible A2/A2B donors because of lack of subtyping.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations